Enhancing health independence of coastal communities through basic health education at SMPN 10 Ternate City [Peningkatan kemandirian kesehatan masyarakat pesisir melalui pendidikan kesehatan dasar di SMPN 10 Kota Ternate] - Abulkhair Abdullah; Muhammad Zulfian A. Disi; Sitti Hartina (Buletin Pengabdian Bulletin of Community Services, 2025)
Limited access to healthcare facilities and low health literacy remains significant challenges, particularly on Hiri Island, North Maluku. SMP Negeri 10 Ternate City is one of the schools on Hiri Island equipped with a school health unit (UKS) room, yet it has not been utilized optimally. This community service initiative aimed to promote health independence among school members by providing education on Clean and Healthy Living Behavior (CHLB) and training in the use of basic medical tools. The methods included CHLB education for students and mentoring for teachers in the operation of sphygmomanometers and digital thermometers, which were also provided as support for the UKS facility. Evaluation was conducted through a pre-test and post-test using a questionnaire consisting of 10 true/false questions. The analysis revealed a significant improvement in students knowledge (p 0.05) regarding CHLB, with average scores increasing from 57.89 (pre-test) to 73.68 (post-test). Furthermore, students enthusiasm during the activities indicated that an interactive educational approach can foster awareness of the importance of healthy living habits. This program not only yielded short-term benefits but also paved the way for sustainability and replication in other schools.